DEVELOPMENT OF AN ECLIPSE-BASED E-MODULE WITH A GUIDED INQUIRY MODEL TO INCREASE STUDENT INTEREST AND LEARNING OUTCOMES IN CLASS XI HIGH SCHOOL DIGESTIVE SYSTEM MATERIAL - Maharani, Helva; Mahadi, Imam (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
This research aims to determine the quality of the Eclipse-based e-module with a guided inquiry model on the digestive system material, as well as to analyze the influence of the Eclipse-based e-module with the guided inquiry model on students' interest and learning outcomes on the digestive system material in class XI SMA. Based on observations, many students find it difficult to understand biological concepts due to the lack of videos and images, e-modules can help students in the learning process. This research consists of two stages, namely the development and implementation stage of an Eclipse-based e-module with a guided inquiry model to increase student interest and learning outcomes in the process of learning digestive system material using Research & Development through the ADDIE (Analysis, Design, Development, Implementation) approach. , and Evaluation). The analysis stage was carried out by observation using a questionnaire and the design stage was carried out using various computer software with the help of Eclipse software. Based on the results of the development and implementation test of the Eclipse-based e-module product with a guided inquiry model, it was found that the quality of the Eclipse-based e-module product with a guided inquiry model was very good, and the increase in interest and learning outcomes in the experimental class increased significantly compared to the control class.